VD_FINDINFO HC / 2017 / 62 vom 20. Dezember 2017 - VD Tribunal cantonal (2017)
CONTRAT INDIVIDUEL DE TRAVAIL, RÉSILIATION IMMÉDIATE, INDEMNITÉEN GÉNÉRAL, DROIT DE LA FONCTION PUBLIQUE, EMPLOYÉ PUBLIC | 337c al. 3 CO, 60 LPers-VD, 61 LPers-VD